2010
DOI: 10.1088/0031-9155/56/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment planning considerations in contrast-enhanced radiotherapy: energy and beam aperture optimization

Abstract: It has been shown that the use of kilovoltage x-rays in conjunction with a contrast agent incorporated into the tumor can lead to acceptable treatment plans with regard to the absorbed dose distribution produced in the target as well as in the tissue and organs at risk surrounding it. In this work, several key aspects related to the technology and irradiation techniques necessary to clinically implement this treatment modality are addressed by means of Monte Carlo simulation. The Zubal phantom was used to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…CERT has been studied by various authors mostly from MC computational and treatment planning standpoints. [30][31][32][33][34][35][36][37][38][39][40] In CERT studies, macroscopic dose enhancement and beam attenuation are computed based on hypothetical planning CT with and without the contrast. Because contrast uptake is typically passive (via tumour microvasculature), endothelial cells are more likely to experience higher dose enhancement than the tumour cells, which are farther away from the microvessels with the contrast.…”
Section: Macroscopic Dose Enhancement and Dose At High-z Interfacesmentioning
confidence: 99%
“…CERT has been studied by various authors mostly from MC computational and treatment planning standpoints. [30][31][32][33][34][35][36][37][38][39][40] In CERT studies, macroscopic dose enhancement and beam attenuation are computed based on hypothetical planning CT with and without the contrast. Because contrast uptake is typically passive (via tumour microvasculature), endothelial cells are more likely to experience higher dose enhancement than the tumour cells, which are farther away from the microvessels with the contrast.…”
Section: Macroscopic Dose Enhancement and Dose At High-z Interfacesmentioning
confidence: 99%
“…13 X-rays of 220 kVp were used as we have previously shown that a X-ray beam with 220-kVp spectrum is an optimal compromise between penetration at depth and sizable fluence in the energy interval that maximized the absorption of the incident beam by the GNPs. 22…”
Section: Absorbed Dose Calculationsmentioning
confidence: 99%
“…A detailed description of how this algorithm is applied to optimization of radiotherapy treatment plans is given in 14 and. 15 Briefly, the algorithm solves the following set of equations:…”
Section: E Treatment Plan Optimizationmentioning
confidence: 99%